Remembering IIUM's 2nd rector, AbdulHamid A. AbuSulayman - Hasan, Md. Mahmudul (The New Straits Times Press (M) Bhd, 2021)
AbuSulayman's commitment to IIUM, in terms of both blood and treasure, was phenomenal. I often hear senior colleagues mention his devotion, hard work and monetary contributions that he made to the university. As Mohd. Kamal Hassan metaphorically stated, IIUM was AbuSulayman's "youngest and most beloved child." In some way, IIUM has been studded with his munificence which he poured out especially upon its needy students. Even after he left the university, his soul was attached to it. We at IIUM are bound by a profound debt of gratitude to AbuSulayman for his sincerity, selflessness and intellectual legacy. We pray that God accepts his good deeds and grants him paradise, and that the university continues to thrive and stay on the track that its early leaders like AbuSulayman defined and constructed.